Time to bring down the twin towers in poor Aboriginal hospital care: addressing institutionalised racism and misunderstandings in communication - Durey, Angela; Thompson, Sandra; Wood, M. (Blackwell Publishing, 2011)
Improvements in Aboriginal health have been slow. Research demonstrates ongoing discrimination towards Aboriginal Australians based on race, including in health services, leads to poor health outcomes. Using an eclectic methodology based on observations and discussions with health practitioners experienced in working with Aboriginal patients, this paper identifies how cross-cultural misunderstandings undermine the quality of care to Aboriginal patients in hospital and offers suggestions for improving practice. It also explores the concept of institutional racism and challenges doctors to reflect on their role in perpetuating power imbalances. We argue that physicians and health care providers need to do more than just deliver evidence-based interventions, by critically reflecting on their own attitudes to and practices with Aboriginal Australians and work collectively to effect systemic change which creates a more inclusive and safe environment for all people accessing health care.